Applications of Fixed Point Theory in Integral Equations and Homotopy Using Partially Ordered S_b Metric Spaces - Ram Prasad, D; Kishore, GNV; Priyanka, K (International Journal of Engineering and Technology, 2018)
In this paper we give some applications to integral equations as well as homotopy theory via SuzukiÂ type fixed point theorems in partially ordered complete Â - metric space by using generalized contractive conditions. We also furnish an example which supports our main result.Â Â